Identifying characteristic features of community orientation among community health nurses in Fiji - Sachiko Tanabe; Satoko Yanagisawa; Silina Waqa-Ledua; Mereani Tukana (Wiley, 2019)
Abstract Aim The present study aimed to identify detailed characteristics of community orientation among community health nurses in Fiji. Design Qualitative descriptive design using semi‐structured individual interviews. Methods Twenty participants including expert nurses, novice nurses, policymakers and representatives from communities were interviewed between July-August 2015 in Fiji. Data were analysed using descriptive qualitative methods. Results Three main themes described in detail characteristics of community orientation among community health nurses in Fiji: Trusting Relationships, Commitment and Activity Management. Trusting Relationships and Commitment were interrelated and served as foundations for community orientation that promoted and facilitated Activity Management. Reflection and a sense of self‐accomplishment in the CHN experiences during Activity Management further strengthened Commitment and Trusting Relationships. Community orientation leads to superior understanding of community health needs, effective use of resources and increased community participation in activities. Such activity management will contribute to promote health beyond the individual, extending to entire communities.